2019
DOI: 10.1111/sjop.12572
|View full text |Cite
|
Sign up to set email alerts
|

“It's been a life‐changing experience!” A qualitative study of young adult cancer survivors’ experiences of the coexistence of negative and positive outcomes after cancer treatment

Abstract: The aim of this study was to illuminate the coexistence of negative and positive experiences of young adult cancer survivors after cancer treatment. Using an interpretive descriptive design, 20 young adult cancer survivors were interviewed. The participants stated that the cancer was a life‐changing experience followed by both negative and positive outcomes. The range of negative outcomes was identified in the main theme “the cancer still hampers me,” subdivided into three subthemes “impaired function and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…Some specific areas of growth mentioned were improved self-reflection, 52 clearer life purpose, 53 a positive new identity, 54 , 55 overall maturation, 56 and increased empathy. 57 Faith in God and spiritual struggles played a significant role in patient personal growth, 58 , 59 mostly by allowing patients to adapt to or comprehend their disease. Social support systems helped promote growth in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some specific areas of growth mentioned were improved self-reflection, 52 clearer life purpose, 53 a positive new identity, 54 , 55 overall maturation, 56 and increased empathy. 57 Faith in God and spiritual struggles played a significant role in patient personal growth, 58 , 59 mostly by allowing patients to adapt to or comprehend their disease. Social support systems helped promote growth in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…No factors were found that decreased gratitude. The three predominant factors that increased gratitude were: having and surviving cancer, 55 , 57 , 148 peer support, 103 , 149 and a strong relationship with their health care provider. 110 , 150 Cancer was described as helping patients appreciate the small things in life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By far the most common theme across articles was that cognitive complaints are associated with difficulties in role functioning 27,35,39,41,44,50,[52][53][54][55][56][57][58][59] . Survivors commonly reported worse concentration, memory, and attention 33,34,40,44,47,52,53,58 and were concerned about the negative impacts of these deficits on employment and education 27,39,40,47,53,58,59 .…”
Section: Role Functioningmentioning
confidence: 99%
“…The global medical lexicon has come a long way in terms of diagnosing and treating different diseases but we have yet to overcome cancer in its advanced stages which often proves fatal. 1 The Latin word 'cancer' literally means a 'crab' owing to the finger-like projections, more formally known as spicules, seen mostly in microscopic analysis of solid malignant tumors. The World Health Organization (WHO) states cancer as the second leading cause of death globally as nearly one in every six deaths is due to this disease.…”
Section: Introductionmentioning
confidence: 99%